Subinguinal versus peritesticular diameters of varicocele veins in the supine and standing posture - Arshad , Muhammad Asharib; Ali Siddiqui, Amjad; Rehman, Khaleeq ur (Journal of the Pakistan Medical Association, 2021)
Objective: Scrotal CDUS is a standard investigation for varicocele patients, but it is not clear that which region should be considered as a standard. The aim of study was to determine that which region should be taken as a standard of measurement for varicocele veins. Methods: The study was conducted at the andro-urology clinic of a teaching hospital. Scrotal Color Doppler Ultrasound (CDUS) parameters were determined at subinguinal and peritesticular region in 35 varicocele patients. The data was collected as mean ± SD and compared using paired t test. Results: In supine position, the mean diameters of varicocele vein at peritesticular region (3.31mm ± 0.70) was compared with the mean diameters of varicocele vein at subinguinal region (2.94mm ± 0.52) and were found to be significantly greater (p < 0.01). The mean diameters of varicocele vein at peritesticular region, when measured in standing posture (3.65mm ± 0.77) was significantly greater (p < 0.01) than the mean diameters at subinguinal region (3.29mm ± 0.62). All varicocele patients had associated semen abnormalities but the diameter of varicocele veins had no significant correlation with semen abnormalities. Conclusion: The varicocele vein diameter at peritesticular region was found to be significantly greater than the sub-inguinal varicocele vein diameter in both lying and standing position. The diameters at peritesticular region may be routinely measured to reach at a better clinical decision. Continuous...